Rooted in the land : essays on community and place - Vitek, William, 1957-; Jackson, Wes, 1936- (Yale University Press, 1996)
Although contemporary society seems to promote the values of individualism and mobility, this engrossing book is dedicated to the notion that human lives are enriched by participation in a social community that is integrated into the natural landscape of a particular place. The 34 contributors-who include David Ehrenfeld, Lynn R. Miller, Wendell Berry, Deborah Tall, David W. Orr, Robert Swann, and Susan Witt, as well as other philosophers, scientists, activists, economists, historians, farmers and ranchers, sociologists, theologians, and political scientists-offer an array of social and ecological perspectives on the nature of "community." The editors, William Vitek and Wes Jackson, contend that a deeper understanding of communities is critical for the health of the planet and the human spirit. They offer a compelling collection of new and classic writings-many in the form of personal narrative-that extend E. F. Schumacher's ideas about the importance of human scale and Aldo Leopold's concept of biotic citizenship. Proposing eloquent defenses of community life and practical suggestions for becoming connected to others and native to a place, the writers explore the loss of community, the philosophical foundations of communities, and the current renewal of community life.